Talent identification and succession planning strategies for the appointment of nursing unit managers: A systematic review - Azam Kamali; Seyed Mojtaba Hosseini; Khalil Alimohammadzadeh; Ali Hassan Shaban Khamseh (Journal of Education and Health Promotion)
Talent acquisition and succession planning are critical to the appointment of nursing managers to ensure high-quality leadership and improved outcomes in healthcare organizations. This review was carried out with the aim of systematically reviewing the literature on talent identification and succession methods for the appointment of nursing unit managers in the Islamic Republic of Iran (IRI). In this study, a comprehensive literature search was conducted using electronic databases, including PubMed, Cochrane Library, PsycINFO, Scopus, Web of Science, and Google Scholar, to identify relevant studies published between 2010 and 2023. The quality assessment of the selected studies was performed using the Critical Appraisal Skills Program (CASP) tool. Moreover, data extraction and synthesis were conducted to summarize the results of included studies. A total of 11 studies were included in this systematic review. The studies selected for this review were interventional (n = 7) and review studies (n = 4). The findings of this review demonstrated that the most important of talent acquisition and succession planning strategies included competency assessment, leadership development programs, coaching programs, and performance evaluation. The strategies are effective in identifying and developing managers of nursing units with high potential. Health policy and health promotion benchmarks emphasize the importance of ensuring a skilled workforce in healthcare settings to provide high-quality care to patients. By implementing talent acquisition and succession planning strategies, healthcare organizations can develop the next generation of nursing unit managers, which will ultimately lead to increased patient satisfaction and improved health outcomes.